Cost–effectiveness of risk assessment and tailored treatment for peripheral arterial disease patients. (August 2014) - Vaidya, Anil; Joore, Manuela A; ten Cate-Hoek, Arina J; Cate, Hugo ten; Severens, Johan L
Aim: The objective of this study was to explore the cost–effectiveness of D-dimer biomarker and the societal value (headroom) of a hypothetical perfect biomarker for risk assessment and subsequent treatment stratification of prophylactic treatment for peripheral arterial disease (PAD).Patients & methods: Decision analytic modeling.Results: Use of the D-dimer biomarker to prescribe oral anticoagulants in the high-risk subset of patients is a cost-effective healthcare intervention. The headroom (societal willingness to pay multiplied by incremental quality-adjusted life years) available for the hypothetical perfect biomarker amounted to €83, 877.Conclusion: D-dimer-based PAD risk assessment and treatment tailoring is cost effective. Identification of high-risk PAD patients and prescription of oral anticoagulants could potentially save substantial costs and improve chances of survival for high-risk PAD patients. However, further research of risk stratifying biomarkers test accuracy is needed to support and strengthen the results of this modeling study.